2012
DOI: 10.1051/epjconf/20123803001
|View full text |Cite
|
Sign up to set email alerts
|

Study of the γ decay of high-lying states in208Pb via inelastic scattering of17O ions

Abstract: Pb by the high resolution measurement of the following gamma decay are also presented in their preliminary form. IntroductionThe use of heavy ions inelastic scattering at approximately 20 MeV/u to study highly excited states (up to the region of the Giant Quadrupole Resonance) is a good tool when the measurement of the subsequent gamma decay is also performed with high resolution. Some partial results of the most recent experiments of this type, performed to investigate the electric-dipole (E1) response of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…A first qualitative comparison to calculations within the relativistic quasiparticle time-blocking approximation (RQTBA) as well as quasiparticle phonon model (QPM) has shown good agreement to the experimental observation [19]: While the low-lying part of the E1 strength shows the described pattern of transition densities, which lead to an enhancement in the isoscalar E1 response, the higher lying states are of transition character towards the GDR and, thus, are suppressed in the isoscalar channel. Meanwhile, similar IS/IV energy behaviour of the low-lying E1 strength has been reported experimentally in inelastic scattering of 17 O off 208 Pb at low bombarding energies [23] as well as in other microscopic model calculations for different nuclei, see e.g. [9,24].…”
supporting
confidence: 84%
“…A first qualitative comparison to calculations within the relativistic quasiparticle time-blocking approximation (RQTBA) as well as quasiparticle phonon model (QPM) has shown good agreement to the experimental observation [19]: While the low-lying part of the E1 strength shows the described pattern of transition densities, which lead to an enhancement in the isoscalar E1 response, the higher lying states are of transition character towards the GDR and, thus, are suppressed in the isoscalar channel. Meanwhile, similar IS/IV energy behaviour of the low-lying E1 strength has been reported experimentally in inelastic scattering of 17 O off 208 Pb at low bombarding energies [23] as well as in other microscopic model calculations for different nuclei, see e.g. [9,24].…”
supporting
confidence: 84%
“…In recent years, several experimental and theoretical investigations, on both stable and radioactive nuclei, were made to learn on the microscopic properties of the pygmy states. An interesting feature of the pygmy states has been observed [5][6][7][8] in a number of different stable nuclei, by comparing results of photon-scattering and α scattering experiments. In particular, it has been found that one group of states is excited in both types of reactions, while another group of states at higher energies is only excited in the (γ, γ ) case [9].…”
Section: Sn Reactionmentioning
confidence: 99%
“…A measurement of the high-lying states in 208 Pb has been made using 17 O beams at 20 MeV/u [30]. The γ decay following inelastic excitation was measured with the detector system AGATA Demonstrator, coupled to an array of large volume LaBr 3 :Ce scintillators and to an array of Si telescope detectors.…”
Section: Pygmy Resonance In 208 Pb By Inelastic Scattering Of 17 O Ionsmentioning
confidence: 99%